The complete mitochondrial genome of a Peruvian creole cattle (Bos taurus) and its phylogenetic analysis - Arbizu Berrocal, Carlos Irvin (2023)
The population of Peruvian creole cattle (PCC) is decreasing mainly due to the introduction of more productive breeds in recent years. We report the complete mitochondrial genome sequence of a PCC bull for the first time. This genome was 16,339 bp in length with the base composition 31.43% A, 28.64% T, 26.81% C, and 13.12% G. It contained 13 protein-coding genes, 2 ribosomal RNA genes, 22 transfer RNA genes and a control region. Among the 37 genes, 28 were positioned on the H-strand and 9 were positioned on the L-strand. The most frequently used codons were CUA (Leucine), AUA (Isoleucine), AUU (Isoleucine), AUC (Isoleucine) and ACA (Threonine). Maximum likelihood analysis clearly demonstrated that PCC are strongly related to a native African breed, giving insights into the maternal ancestry of PCC. The annotated mitochondrial genome of PCC would serve as an important genetic data set for further breeding work and conservation strategies.